Peculiarities of accounting for merchandise costs in Badoer’s Ledger - Petrash , Nikolai I. (De Computis, Revista Española de Historia de la Contabilidad., 2026)
The Spexe de marchadantia account, employed in commercial accounting during the 14th and 15th centuries, has long provoked scholarly debate, though few researchers examined it systematically. Modern analysis of this account in Jacomo Badoer’s Libro dei conti (1436–1439) faces substantial challenges: significant material deterioration and damage to the archival source have obscured critical accounting entries. Through digital reconstruction techniques, the authors recovered previously unreadable text and restored informational losses in the ledger. This methodological approach enabled comprehensive analysis of Badoer’s accounting procedures, revealing that the Spexe de marchadantia account functioned as both an expense distribution mechanism and a significant profit-generating instrument through commission fees and markup accumulation. The digital methodology thus transforms damaged historical sources into analyzable datasets, offering new interpretative possibilities for understanding pre-Pacioli accounting sophistication.